Exports and Productivity: An Empirical Analysis of German and Austrian Firm-Level Performance - Thorsten Hansen (Ludwig-Maximilians-Universität München, Volkswirtschaftliche Fakultät, 2010)
This paper studies the relationship between export activities and firm-level productivity. Unique matching of German and Austrian micro data from 1994 to 2003 suggests that exporters are more productive by around 40 percent compared with non-exporters. Moreover, beside other analysis techniques, instrumental variable estimations suggest that exporting causes a rise in firm-level productivity. That is, the annual average growth rate of an exporting firm's productivity is between about 1 and 1.5 percent higher than that of non-exporters. It allows the conclusion that, against other findings of existing studies, both directions hold: more productive firms self-select themselves into export markets and being active in foreign markets boosts firm-level productivity.
urn:nbn:de:bvb:19-epub-11466-7
Keywords: D24; F13; F23; L22; L23; O47; 330; exports; firm-level productivity; Exportwirtschaft; Produktivität; Vergleich; Industrie; Schätzung; Deutschland